Les violences seigneuriales dans les Grandes Chroniques de France de Jean de France duc de Normandie : première approche - Christiane Raynaud (Criminocorpus)
John duke of Normandy’s Grandes chroniques de France, before 1350, make room for ancient seigniorial violence, predations, assassinations and private wars. Rare images present them as a seignorial social grouping, often intrafamilial relationship between aristocrats, counts and barons with their military entourage. Poor and inermes hardly appear. Put in difficulties lords, some ladies and prelates complain to the king and his council, leading to the intervention of the royal ost which is no longer quite feudal. In order to bring the notorious and recidivist troublemakers who controlled castles to resignation, dreadful pacification operations and the strict exercise of justice were supervised. This struggle against the tyrants of the poor and the churches, following the exemple of the tireless Louis VI, is revisited in the light of contemporary realitites. In the face of the uncertain loyalty and the claims and demands of a restive nobility, that John tries to rally or submit, a program is defined: through the restoration of peace, a primordial aspect of his plan for government and reform, the future king asserts his legitimacy.